The Constitutional Foundation of Communal Justice - Ruiz Molleda, Juan Carlos (2009)
This work intends to analyze the constitutional basis of communal justice through the study of what is established in the Constitution, the set of constitutional provisions, the jurisprudence of the Peruvian Constitutional Court on the subject and norms of protection of human rights with respect to communal justice, focusing on developing the scope and constitutional limits of communal justice. In the first part, the concept of communal justice is developed, which will be used as a basis for the later part of the article. After that, it explains the consequences of a literal and isolated interpretation of Article 149 of the Peruvian Constitution, which leads to inaccurate considerations. In the third part, criticisms are made of the literal interpretation that has been developed and it is demonstrated that its use is not feasible or adequate to study communal justice in a correct manner. Subsequently, certain constitutional principles that should guide the subject study of the article are explained. In the fifth part, the right to communal identity is developed as a support for communal justice and the possibility of exercising the right of access to justice and judicial protection. Finally, an interpretation based on constitutional principles is developed that manages to build and fill the content of communal justice, making it a mechanism for rural populations to exercise and protect the constitutional rights that the State seeks to protect.